Stress Level and Smoking Behavior - Zakiyah Zakiyah; Yolanda Anastasia Sihombing; Muh Ihsan Kamaruddin; Glendy Ariando Salomon; Muhammad Anshari (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Stress is one of the common mental health problems in today's society. This study aimed to investigate the relationship between stress levels and smoking behavior. Smoking is a habit that is detrimental to health and can be a risk factor for a variety of serious diseases. However, many individuals who smoke may claim that smoking is their way of coping with stress. Data for the study were obtained through interviews and questionnaires given to several participants involved in smoking behavior. The data collected included stress levels, smoking history, and motivation to smoke. The results showed that there was a significant relationship between stress levels and smoking behavior. Individuals who experience higher levels of stress tend to be more likely to smoke or smoke more frequently. In addition, the study also revealed that many smoking participants reported that they smoked as a way to cope with stress. This study has important implications for treatments and interventions in reducing smoking. Understanding that stress can be a trigger for smoking can help in designing more effective evidence-based programs to help individuals cope with stress without having to rely on cigarettes. Better prevention and treatment efforts for individuals who smoke should also consider stress management as an important part of treatment. As such, the study could provide a better view of the complex relationship between stress and smoking and provide a foundation for better public health improvements in tackling the smoking problem